Separate repayment enforcement rights of minority lenders In defaulting syndicated loans - Mbangi, Lelethu (University of the Witwatersrand, Johannesburg, 2018)
A syndicated loan is one where two or more Banks separately lend to one borrower in terms of a single facility agreement concluded between the Banks, the borrower, the borrower’s guarantors and the arranger or agent. The single facility agreement is a recordal of terms of the loan made available by each of the Banks forming part of the syndicate to the borrower. Taking deposits from the public is the primary business of a Bank, lending is the secondary business of a Bank. Though Banks are dominant participants in syndicated lending, there are now other participants such as fund managers and insurance companies who also have financial resources to participate just like Banks. The purpose of syndicated lending, from a Banks’ perspective, is firstly to avoid large single exposure to one borrower and secondly to participate in a loan which a Bank on its own would not have been able to make available to the borrower. By its nature syndicated lending contemplates an arrangement whereby participants will either fall into the category of being a majority or minority lender. The manner in which the Loan Market Associations’ (“LMA”) standardised facility agreements are framed, favour the majority lenders as far as decision making is concerned. The most crucial event which its treatment depends on the decision of majority lenders is the borrowers’ payment default. The conflict between the decisions of the majority and minority lenders on treatment of payment default by a borrower/s causes a legal dispute. The issue in dispute is usually the interpretation of clauses providing for separate repayment enforcement rights of minority lenders. The decisions in the cases analysed further below demonstrate the limited separate repayment enforcement rights and decision making powers of minority lenders in instances where there is a payment default by a borrower/s. Separate repayment enforcement rights and decision making clauses are suggested to extricate minority lenders from commercial decision of majority lenders which are in conflict with theirs. The suggested clauses are structured in such a way that legal conflict between the lenders is diffused by viable commercial alternatives available to each of them.
Dissertation submitted in partial fulfilment of the requirements of the Degree of Master of Law (LLM), to the Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2018
Keywords: Syndicated loan; Loan Market Associations’ (“LMA”); Minority lenders; Commercial law; Business law; UCTD; SDG-8: Decent work and economic growth; SDG-4: Quality education